TEORI INVESTASI DAN PERTUMBUHAN EKONOMI DALAM EKONOMI PANCASILA - Mubyarto, Mubyarto (Journal of Indonesian Economy and Business, 2003)
If economics is to become less of a religion and more of a science, then the foundationsof economics should be torn down and replaced. (Steve Keen, 2001, Debunking Economics:The Naked Emperor of the Social Sciences, Pluto Press, Sydney).Keywords: Religions Economics, Economic Sin.